Między postprawdą a (pseudo)mądrością tłumu – o epistemicznej pułapce cyfrowych mediów i analogowych kompetencjach jako środkach jej uniknięcia - PIETRZYKOWSKI, ADAM (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Adam Pietrzykowski, Między post-prawdą a (pseudo)mądrością tłumu – o epistemicznej pułapce cyfrowych mediów i analogowych kompetencjach jako środkach jej uniknięcia [Between post-truth and (pseudo)wisdom of the crowds – on epistemic trap of digital media and analog competences as means of avoiding it]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 77-91. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.04 In the modern world, truth has become an anachronistic value. At the same time, hopes associated with its restitution by the networked crowd have proved futile. The growing dominance of audiovisual media inevitably leads to the formation of a new man, driven more by affection than rationality. Phenomena such as secondary illiteracy, language depletion and the rise of populism are signs of this process. The development of media literacy suggested by theoreticians of education may be an insufficient remedy for the indicated civilization problem. The solution may be returning to basic competences shaped, in particular, by philosophical education, which may become the proper medium for restoring critical reason in society.